Carbon material, conductive composition using same, and conductive film

A nitrogen-doped carbon material with optimized nitrogen content and structure addresses the conductivity limitations of conventional carbon materials, achieving low volume resistivity and improved conductive properties.

JP7604861B2Active Publication Date: 2024-12-24TOYO INK MFG CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2020201217
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-03
Publication Date
2024-12-24
Estimated Expiration
2040-12-03

AI Technical Summary

Technical Problem

Conductive carbon materials exhibit higher volume resistivity compared to metal fillers, limiting their use in conductive applications, and existing nitrogen doping methods require high temperatures, impacting energy consumption and cost.

Method used

A nitrogen-doped carbon material with specific nitrogen-to-carbon ratios and nitrogen atom types, optimized surface characteristics, and controlled crystallinity, achieved through controlled heat treatment and doping processes, enhances conductivity.

Benefits of technology

The nitrogen-doped carbon material achieves a volume resistivity of 2.0×10^-3 Ω·cm or less, improving conductivity and maintaining crystallinity, suitable for conductive compositions and films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007604861000001
    Figure 0007604861000001
  • Figure 0007604861000002
    Figure 0007604861000002
  • Figure 0007604861000003
    Figure 0007604861000003
Patent Text Reader

Abstract

To provide a carbon material excellent in conductivity.SOLUTION: The ratio (N / C) of nitrogen elements to carbon elements in a carbon material doped so that a nitrogen element substitutes at least a part of carbon elements in a carbon frame is 0.01-20 mol%. The ratio (surface N3) of N3 type nitrogen atoms to the total nitrogen atoms on the surface of the carbon material, measured by X ray photoelectron spectroscopy (XPS) is 10 mol% or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a carbon material, and a conductive composition and a conductive film using the same. [Background technology]

[0002] In recent years, electronics has developed remarkably, and conductive materials used in various electronic devices are also required to be smaller, lighter, less expensive, and have a longer life under various usage environments. For example, when manufacturing the wiring for electronic device substrates or wiring for connecting electronic devices, a conductive composition with good conductivity is required, but conductive compositions using metal fillers such as silver and copper are generally used, and major issues such as cost and durability have yet to be resolved. On the other hand, various studies have been conducted on conductive compositions using conductive carbon materials that do not use metals, but due to insufficient conductivity, their use has been limited to semi-conductive applications such as antistatic applications.

[0003] As conductive carbon materials, highly conductive carbons such as graphite and carbon nanotubes have also been considered. The volume resistivity of these highly conductive carbons is 10 -2 It has excellent electrical conductivity of less than Ω·cm, and it has been reported that the electrical conductivity issue can be improved compared to conventional materials (Patent Documents 1 and 2). However, the volume resistivity is 10 -4 Compared with metal fillers that exhibit extremely high electrical conductivity of less than Ω·cm, the volume resistivity is significantly higher, and improving electrical conductivity was a major challenge.

[0004] Here, the electrical conductivity (σ) of the carbon material is expressed by the following formula. σ=μ×n×e (Formula 1) μ: mobility, n: carrier density, e: elementary charge (constant) From the above formula (1), in order to improve the electrical conductivity, it is necessary to improve the mobility and / or carrier density.

[0005] Therefore, by doping carbon materials with hetero elements such as boron and nitrogen, it is expected that the carrier density can be improved by introducing electrons or holes. Although it has been reported that carbon materials can be made highly conductive by doping with boron (Patent Document 3), there are problems in terms of energy consumption and cost because high temperatures of 2000°C or higher are required during production. On the other hand, although there is a report on the catalytic activity of nitrogen doping (Patent Document 4), there is a lack of research focusing on electrical conductivity, and the relationship between the content and bonding state of nitrogen in carbon materials and electrical conductivity has not yet been clarified. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 3-7740 [Patent Document 2] JP 2008-293821 A [Patent Document 3] International Publication No. WO2014 / 185496 Brochure [Patent Document 4] JP 2014-207220 A Summary of the Invention [Problem to be solved by the invention]

[0007] In view of the above problems, an object of the present invention is to provide a carbon material having excellent electrical conductivity. [Means for solving the problem]

[0008] The present inventors have conducted extensive research to solve the above-mentioned problems, and as a result, have arrived at the present invention. That is, the present invention relates to a carbon material doped with nitrogen elements so as to substitute at least a portion of the carbon elements in the carbon skeleton, characterized in that the ratio of nitrogen elements to carbon elements in the carbon material (N / C) is 0.01 to 20 mol %, and the ratio of N3-type nitrogen atoms to total nitrogen on the surface of the carbon material (surface N3), as measured by X-ray photoelectron spectroscopy (XPS), is 10 mol % or more.

[0009] In the present invention, the ratio (mol%) of nitrogen elements to all elements on the surface of the carbon material measured by X-ray photoelectron spectroscopy (XPS) is defined as N, and the sum (mol%) of the ratio of N1 type nitrogen atoms and the ratio of N2 type nitrogen atoms to all nitrogen on the surface of the carbon material is defined as (N 1 +N 2 ), {N×(N 1 +N 2 The carbon material is characterized in that the proportion of surface terminal nitrogen, represented by the formula {(a) / (b)}=1 mol % or less.

[0010] The present invention also relates to the carbon material, wherein the ratio of nitrogen elements to carbon elements on the surface of the carbon material (surface N / C) measured by X-ray photoelectron spectroscopy (XPS) is 0.2 to 1.3 mol %.

[0011] In addition, the present invention is directed to a method for determining the BET specific surface area (BET N2 ) is 0.01 to 100m 2 / g.

[0012] The present invention also relates to the above carbon material, characterized in that in an X-ray diffraction pattern obtained using CuKα rays as an X-ray source, the carbon material has a peak at a diffraction angle (2θ) of 24.0 to 27.0° and a half-value width of the peak is 8° or less.

[0013] The present invention also relates to a conductive composition containing the carbon material and a binder.

[0014] The present invention also relates to a conductive film obtained by using the conductive composition. Effect of the Invention

[0015] According to the present invention, a nitrogen-doped carbon material having excellent electrical conductivity can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The present invention will be described in detail below. In this specification, a "nitrogen-containing carbon material doped with nitrogen elements so as to substitute at least a part of the carbon elements in the carbon skeleton" may be simply referred to as a "nitrogen-doped carbon material".

[0017] <Nitrogen-doped carbon materials> The nitrogen-doped carbon material of the present invention will be described. The nitrogen-doped carbon material is a material that has a basic skeleton of a carbon hexagonal mesh plane in which carbon atoms are covalently bonded to form a hexagonal mesh-like mesh plane, has physical and chemical interactions (bonds) between the structural units, and contains nitrogen elements, and is a carbon material containing nitrogen elements doped to replace at least a part of the carbon elements. Note that "nitrogen elements doped to replace carbon elements" refers to nitrogen elements that replace carbon elements in the carbon hexagonal mesh plane, nitrogen elements that replace carbon elements at the edges of the carbon hexagonal mesh plane on the surface of the carbon material, nitrogen elements that are bonded to carbon elements such as defects and defects that exist as vacancies in the carbon hexagonal mesh plane on the surface of the carbon material, and nitrogen elements that are bonded to carbon elements to bridge between the faces of the carbon hexagonal mesh plane near the surface of the carbon material, and these nitrogen elements can be measured by X-ray photoelectron spectroscopy (XPS) described later.

[0018] In the nitrogen-doped carbon material of the present invention, the ratio of the content of nitrogen element to the content of carbon element in the carbon material (N / C) is 0.01 to 20 mol%, preferably 0.1 to 5 mol%, more preferably 0.1 to 2 mol%, further preferably 0.1 to 1 mol%, and particularly preferably 0.15 to 0.5 mol%. When N / C is 0.01 mol% or more, the carrier density is improved, and thus the electrical conductivity is improved. When N / C is 20 mol% or less, the crystallinity of the carbon material is high, and thus the carrier mobility is good. The contents of carbon element and nitrogen element in the nitrogen-doped carbon material can be determined by CHN element analysis or the like. The nitrogen content in the nitrogen-doped carbon material indicates the total amount of nitrogen contained on the surface and inside, and includes nitrogen doped to replace nitrogen compounds and carbon elements.

[0019] The nitrogen-doped carbon material of the present invention has a ratio of N3 type nitrogen atoms to the total nitrogen on the surface of the carbon material (surface N 3 ) is 10 mol % or more. N3 type nitrogen atoms are quaternary nitrogen atoms bonded to three carbon atoms, as described below. The ratio of N3 type nitrogen atoms to the total nitrogen on the carbon material surface (surface N 3 ) can be measured by X-ray photoelectron spectroscopy (XPS) and can be calculated from the ratio of the peak area of ​​N3 type nitrogen atoms to the N1s spectrum area of ​​nitrogen.

[0020] The N1s spectrum of nitrogen obtained by XPS measurement appears in the binding energy range of the N1s electron of the nitrogen element (around 390 to 410 eV) and is known to consist of four components shown in the structural formula below. The binding energy values ​​(peak tops) of each component are 398.5 ± 0.5 eV for N1 type nitrogen atoms with a pyridine-like structure, 400 ± 0.5 eV for N2 type nitrogen atoms with a pyrrole-like structure, 401 ± 0.5 eV for quaternary N3 type nitrogen atoms bonded to three carbon atoms, and 404.0 ± 0.5 eV for N4 type nitrogen atoms bonded to heterogeneous elements such as oxygen in an oxidized state. When these peaks overlap, the peak intensity, peak position, and full width at half maximum of each component are optimized as parameters using a Gaussian function, and the peaks can be fitted to separate the peaks to determine the ratio. In this way, the ratio of each component to the total amount of nitrogen on the carbon material surface can be determined by N1s peak separation.

[0021] [ka]

[0022] In the nitrogen-doped carbon material of the present invention, the ratio of the amount of N3-type nitrogen atoms to the total amount of nitrogen on the material surface (surface N 3 ) is preferably 20 mol % or more, more preferably 30 to 90 mol %, and further preferably 50 to 80 mol %. Since N3 type nitrogen atoms use their unshared electron pairs to bond with carbon, they can donate electrons to the carbon material, thereby improving the carrier density of the carbon material. On the other hand, since N1 type nitrogen atoms and N2 type nitrogen atoms have unshared electron pairs, their electron-donating effect on the carbon material is significantly small. Furthermore, since N4 type nitrogen atoms are bonded to heterogeneous elements such as oxygen, their electron-donating effect on the carbon material is small. Therefore, the proportion of N3 type nitrogen atoms (surface N 3 When the content of nitrogen is 10 mol %, the decrease in crystallinity and the inhibition of electronic conduction caused by other nitrogen atoms can be suppressed.

[0023] The ratio (mol%) of nitrogen elements to all elements on the carbon material surface measured by XPS was defined as N, and the sum (mol%) of the ratio of N1 type nitrogen atoms and the ratio of N2 type nitrogen atoms to all nitrogen on the carbon material surface was defined as (N 1 +N 2 ), {N×(N 1 +N 2 By keeping the proportion of surface terminal nitrogen (surface terminal nitrogen amount) represented by {(amount of surface terminal nitrogen) at 1 mol% or less, the crystallinity of the carbon material and the continuity of the π bonds in the carbon hexagonal mesh plane can be maintained, and high carrier mobility can be maintained. The proportion of each element on the surface of the carbon material can be calculated from the ratio of the spectral area of ​​each element to the spectral area of ​​all elements.

[0024] Furthermore, the ratio of nitrogen elements to carbon elements on the surface of the carbon material (surface N / C) measured by XPS is preferably 0.1 to 5.0 mol%, more preferably 0.2 to 1.3 mol%. When the ratio of nitrogen elements to carbon elements on the surface of the carbon material is 0.1 mol% or more, the conductivity is improved due to the carrier doping effect, and when it is 5.0 mol% or less, the hexagonal carbon mesh surface structure on the surface is maintained, improving the conductivity between particles.

[0025] The nitrogen-doped carbon material of the present invention may contain metal elements, but from the viewpoints of easy disposal, light weight, and environmental protection, it is preferable that it does not contain metal elements. The ratio of metal elements to carbon elements on the surface of the carbon material (surface metal amount) measured by XPS is preferably 1.0 mol % or less, more preferably 0.5 mol % or less, and even more preferably 0.1 mol % or less.

[0026] In addition, the nitrogen-doped carbon material of the present invention has a BET specific surface area (BET N2 ) is 0.01 to 100m 2 / g, more preferably 0.1 to 20m 2 / g, more preferably 1 to 10m 2 / g. BET N2 100m 2When the BET ratio is 0.1 to 0.25, the number of particles per unit weight and volume is small, so that the contact resistance between particles is reduced and good electrical conductivity is obtained. N2 is 0.01m 2 When the nitrogen doping ratio is 1 / g or more, the nitrogen doping reaction proceeds easily.

[0027] The specific surface area in the present invention refers to the surface area per unit mass of a sample, and can be determined by a gas adsorption method. The analysis method is the BET method, and the relative pressure (P (adsorption equilibrium pressure) / P 0 The BET specific surface area can be calculated by determining the monomolecular adsorption amount from the intercept and gradient of the line obtained by plotting (saturated vapor pressure) = 0.05 to 0.3) versus the gas adsorption amount.

[0028] In addition, in the X-ray diffraction (XRD) diagram of the carbon material obtained using CuKα radiation as the X-ray source, the (002) diffraction peak of carbon that appears at around 24.0 to 27.0° can be seen to be a carbon material with a carbon hexagonal mesh plane as the basic skeleton. The position of the (002) diffraction peak of carbon changes depending on the interplanar distance of the carbon hexagonal mesh planes, and the higher the peak position is on the higher angle side, the closer the distance of the carbon hexagonal mesh planes is, indicating a high degree of graphitic regularity in the structure. In addition, the sharper the peak (the smaller the half-width), the larger the crystallite size and the more developed the crystal structure.

[0029] When the half-width (full width at half maximum) of the peak is 8° or less, the carbon material has high crystallinity and high electronic conductivity, which is preferable. It is more preferable that the half-width of the peak is 4° or less, and even more preferable that it is 1° or less. When the peak overlaps with a nearby peak, the peak is separated by fitting, and the half-width is calculated.

[0030] The average interplanar distance d002 calculated from the obtained peak is preferably 0.338 nm or less, and more preferably 0.336 nm or less. In general, carbon materials tend to have better electrical conductivity as the average interplanar distance d002 is smaller.

[0031] The structure (shape) of the nitrogen-doped carbon material of the present invention is not particularly limited as long as it is a carbon material that satisfies the above-mentioned conditions. For example, it is classified into carbon black (acetylene black, ketjen black, furnace black, medium thermal carbon black, graphitized carbon black), graphite, graphene nanoplatelets, graphene, carbon fiber, carbon nanotube, carbon nanofiber, carbon nanohorn, carbon nanobrush, activated carbon, porous carbon, nanoporous carbon, etc., and is preferably graphitized carbon black, graphite, graphene nanoplatelets, graphene, carbon fiber, carbon nanotube, carbon nanofiber, and more preferably graphite, graphene nanoplatelets, graphene, carbon nanotube.

[0032] In addition, the nitrogen-doped carbon material of the present invention has a volume resistivity of 2.0×10 -3 It is preferable that the resistivity is Ω·cm or less.

[0033] <Method for producing nitrogen-doped carbon material> The method for producing the nitrogen-doped carbon material in the present invention is not particularly limited, and A method of mixing and carbonizing a carbonaceous raw material and a compound containing a nitrogen element; A method for carbonizing a carbonaceous raw material containing a nitrogen element, A method for carbonizing a compound containing a nitrogen element, such as a macrocyclic compound such as phthalocyanine or porphyrin, A conventional method can be used, such as a method of doping a carbonaceous raw material with nitrogen element by a vapor phase method.

[0034] Preferred production methods include a method of heat-treating a carbonaceous raw material containing nitrogen, a method of mixing at least a carbonaceous raw material with a compound containing nitrogen and heat-treating the mixture, a method including a step of washing with an acid and drying the nitrogen-doped carbon material obtained by the heat treatment, and a method including a step of heat-treating the nitrogen-doped carbon material obtained by the acid washing.

[0035] Next, the carbon source used in the production of the nitrogen-doped carbon material will be described. The carbon source is not particularly limited, but may be an inorganic carbon source or an organic carbon source, and is preferably an inorganic carbon source.

[0036] Specific inorganic carbon sources include carbon black (acetylene black, ketjen black, furnace black, medium thermal carbon black, graphitized carbon black), graphite, graphene nanoplatelets, graphene, carbon fiber, carbon nanotubes, carbon nanofibers, carbon nanohorns, carbon nanobrushes, activated carbon, porous carbon, nanoporous carbon, and the like. Graphitized carbon black, graphite, graphene nanoplatelets, graphene, carbon fiber, carbon nanotubes, carbon nanofibers, and more preferably graphite, graphene nanoplatelets, graphene, and carbon nanotubes are used. Among the above carbon sources, the size and lamination structure of the carbon hexagonal mesh surface vary depending on the type and manufacturer, and the crystallinity, particle size, shape, BET specific surface area, pore volume, pore size, bulk density, DBP oil absorption, surface acid-basicity, surface hydrophilicity, and electrical conductivity, as well as various physical properties and costs vary, so that an optimal material can be selected according to the application and required performance.

[0037] Examples of commercially available graphite that can be used include, but are not limited to, CMX, UP-5, UP-10, UP-20, UP-35N, CSSP, CSPE, CSP, CP, CB-150, CB-100, ACP, ACP-1000, ACB-50, ACB-100, ACB-150, SP-10, SP-20, J-SP, SP-270, HOP, GR-60, LEP, F#1, and F#2 manufactured by Nippon Graphite Industries Co., Ltd. , F#3, CGC-20, CGC-50, CGB-20, CGB-50, PAG-60, PAG-80, PAG-120, PAG-5, HAG-10W, HAG-150, etc. manufactured by Ito Graphite Industries Co., Ltd., EC1500, EC1000, EC500, EC300, EC100, EC50, etc. manufactured by Chuetsu Graphite Co., Ltd., CX-3000, FBF, BF, CBR, SSC-3000, SSC-600, SSC-3, SSC, CX- 600, CPF-8, CPF-3, CPB-6S, CPB, 96E, 96L, 96L-3, 90L-3, CPC, S-87, K-3, CF-80, CF-48, CF-32, CP-150, CP-10 0, CP, HF-80, HF-48, HF-32, SC-120, SC-80, SC-60, SC-32, RA-3000, RA-15, RA-44, GX-600, G-6S, G-3, G-150, G -100, G-48, G-30, G-50, SGP-100, SGP-50, SGP-25, SGP-15, SGP-5, SGP-1, SGO-100, SGO-50, SGO-25, SGO-15, SGO-5, SGO-1, SGX-100, SGX-50, SGX-25, SGX-15, SGX-5, SGX-1 and the like manufactured by SEC Carbon Co., Ltd., and 10099M and PB-99 manufactured by Nishimura Graphite Co., Ltd. In addition, commercially available carbon black that can be used is not particularly limited, but examples thereof include Ketjen Black EC-300J, EC-600JD, Lionite EC-200L, etc., manufactured by Lion Specialty Chemicals; Furnace Black #2350, #2600, #3050B, #3030B, #3230B, and #3400B, etc., manufactured by Mitsubishi Chemical Corporation; and Acetylene Black HS-100 and FX-35, etc., manufactured by Denka Company. In addition, commercially available carbon nanotubes that can be used include single-walled carbon nanotubes, double-walled carbon nanotubes, multi-walled carbon nanotubes, etc., and include, but are not limited to, VGCF-H, VGCF-X, etc. manufactured by Showa Denko K.K., carbon nanotubes manufactured by Meijo Nano Carbon Co., Ltd., NTP3003, NTP3021, NTP3121, NTP8012, NTP8022, NTP9012, NTP9112, etc. manufactured by NTP Corporation, and TUBALL manufactured by OCSiAl Corporation. In addition, commercially available graphene-based carbon that can be used is not particularly limited, but examples thereof include graphene nanoplatelets xGnP-C-300, xGnP-C-500, xGnP-C-750, xGnP-M-5, xGnP-M-15, xGnP-M-25, xGnP-H-5, xGnP-H-15, and xGnP-H-25 manufactured by XG Sciences.

[0038] Among these carbon sources, it is preferable to use graphite, graphene nanoplatelets, graphene, and carbon nanotubes from the viewpoints of electrical conductivity and cost, and it is more preferable to use graphite.

[0039] In addition, the specific organic carbon source is not particularly limited as long as it is an organic carbon raw material that is carbonized to carbon particles after heat treatment, but specific examples include phenolic resins, polyimide resins, polyamide resins, polyamideimide resins, polyacrylonitrile resins, polyaniline resins, phenol formaldehyde resins, polyimidazole resins, polypyrrole resins, polybenzimidazole resins, melamine resins, pitch, coke, lignite, polycarbodiimide, biomass, proteins, humic acid, and derivatives thereof. Among these, the use of pitch and coke, which are also used as raw materials for graphite, is preferred.

[0040] Next, the nitrogen source used in the production of the nitrogen-doped carbon material will be described. The nitrogen source is not particularly limited as long as it is a compound containing a nitrogen element. For example, organic compounds such as dyes and polymers, inorganic compounds such as ammonia, etc. may be used alone or in combination of two or more. Nitrogen-containing aromatic compounds are preferred because they can easily introduce nitrogen elements into the carbon material efficiently. Specifically, macrocyclic compounds such as phthalocyanine compounds, naphthalocyanine compounds, porphyrin compounds, and tetraazaannulene compounds may be used. The aromatic compounds may be those into which an electron-withdrawing functional group or an electron-donating functional group has been introduced. In particular, phthalocyanine compounds are particularly preferred as raw materials because various compounds are available at low cost. Among them, cobalt phthalocyanine compounds, nickel phthalocyanine compounds, iron phthalocyanine compounds, and metal-free phthalocyanine compounds are more preferred from the viewpoint of cost.

[0041] The raw material composition ratio of the carbon source and the nitrogen source for producing a nitrogen-doped carbon material is not particularly limited as long as the nitrogen content can be obtained as described above. However, the ratio of the nitrogen source to 100 parts by mass of the carbon source is preferably 0.1 to 100 parts by mass, and more preferably 1 to 50 parts by mass.

[0042] The method for mixing the carbon source and the nitrogen source is not particularly limited, but is preferably dry mixing or wet mixing. As a mixing device, the following dry mixing device or wet mixing device can be used.

[0043] Examples of dry mixing devices include roll mills such as two-roll and three-roll devices, high-speed agitators such as Henschel mixers and super mixers, fluid energy pulverizers such as Micronizers and jet mills, attritors, particle composite devices manufactured by Hosokawa Micron Corporation such as "Nanocure," "Nobilta," and "Mechanofusion," and powder surface modification devices manufactured by Nara Machinery Manufacturing Co., Ltd. such as "Hybridization System," "Mechano Micros," and "Miraro." In addition, when using a dry mixer, the other raw materials may be added directly in powder form to the base raw material powder, but in order to prepare a more uniform mixture, the other raw materials may be dissolved or dispersed in a small amount of solvent in advance and then added while breaking up the agglomerated particles of the base raw material powder. In order to further increase the efficiency of the process, the raw materials may be heated.

[0044] Examples of wet mixing devices include mixers such as Disper, Homomixer, or Planetary Mixer, homogenizers such as M-Technique's "Clearmix" or PRIMIX's "Filmix", Red Devil's paint conditioner, ball mill, sand mills such as Shinmaru Enterprises' "Dynomill", attritor, or Coball Mill, media-type dispersers, wet jet mills such as Genus' "Genus PY", Sugino Machine's "Starburst", Nanomizer's "Nanomizer", media-less dispersers such as M-Technique's "Clear SS-5" or Nara Machinery's "Micros", or other roll mills, kneaders, etc., but are not limited thereto. In addition, it may be preferable to use a wet mixing device that has been treated to prevent metal from entering the device. For example, when using a media type disperser, it is preferable to use a method using a disperser whose agitator and vessel are made of ceramic or resin, or a disperser whose metallic agitator and vessel surface are treated with tungsten carbide spraying, resin coating, or the like. As the media, it is preferable to use ceramic beads such as glass beads, zirconia beads, or alumina beads. Also, when using a roll mill, it is preferable to use a ceramic roll. Only one type of dispersing device may be used, or multiple types of devices may be used in combination.

[0045] Furthermore, if the raw materials are not uniformly dissolved or dispersed, a dispersant may be added as necessary to improve the wettability and dispersibility of each raw material in the solvent, thereby dispersing and mixing the raw materials.

[0046] The conditions for heat-treating the mixture of the carbon source and the nitrogen source vary depending on the types and amounts of the carbon source and the nitrogen source used as raw materials, and are not particularly limited, but the heating temperature is preferably 500 to 1700° C., more preferably 600 to 1500° C., and even more preferably 800 to 1300° C. In addition, the heating time is not particularly limited, but is 10 minutes to 72 hours, and preferably 30 minutes to 10 hours.

[0047] The atmosphere in the heat treatment step is preferably an inert gas atmosphere such as nitrogen or argon, a reducing gas atmosphere in which hydrogen is mixed with nitrogen or argon, or a vacuum atmosphere in order to prevent side reactions such as oxidation of the raw material. Nitrogen may also be doped by a gas phase method in an ammonia gas atmosphere containing a large amount of nitrogen element.

[0048] Furthermore, the heat treatment step may not only be a treatment step carried out in one stage at a constant atmosphere, temperature and time, but also a treatment step carried out in multiple stages with different atmospheres, temperatures and times.

[0049] The method for producing the nitrogen-doped carbon material further includes a method including a step of washing the nitrogen-doped carbon material obtained by the heat treatment with an acid and drying it. The acid used here is not particularly limited as long as it can dissolve the metal components, but concentrated hydrochloric acid or dilute sulfuric acid, which has low reactivity with the carbon material and strong dissolving power of the metal components, is preferable. A specific washing method is to add an acid to a glass container, add the nitrogen-doped carbon material, and stir for several hours while dispersing, then leave it to stand and remove the supernatant. Then, the above method is repeated until the color of the supernatant is no longer confirmed, and finally, the acid is removed by filtration and washing with water, and the mixture is dried. Washing with an acid is preferable because it removes the metal components.

[0050] The method for producing the nitrogen-doped carbon material further includes a method including a step of heat-treating the nitrogen-doped carbon material obtained by the acid washing again. The heat treatment here does not differ significantly from the conditions of the previous heat treatment. The heating temperature is preferably 500 to 1700°C, more preferably 600 to 1500°C. In addition, the atmosphere is preferably an inert gas atmosphere such as nitrogen or argon, a reducing gas atmosphere in which hydrogen is mixed with an inert gas, an ammonia gas atmosphere containing a large amount of nitrogen element, etc., from the viewpoint of preventing the nitrogen element on the surface from being decomposed and reduced.

[0051] <Conductive composition> The conductive composition of the present invention contains a nitrogen-doped carbon material and a binder, and may also contain a solvent, if necessary.

[0052] (binder) In the conductive composition of the present invention, the binder is used to bind particles such as nitrogen-doped carbon material. As the binder, a conventionally known binder can be used, for example, acrylic resin, polyurethane resin, polyester resin, polyvinyl resin, polysaccharide, polyamino acid resin, polyether resin, phenol resin, epoxy resin, phenoxy resin, urea resin, melamine resin, alkyd resin, formaldehyde resin, silicon resin, fluororesin, synthetic rubber such as styrene-butadiene rubber and fluororubber, conductive resin such as polyaniline and polyacetylene, etc., and polymer compounds containing fluorine atoms such as polyvinylidene fluoride, polyvinyl fluoride, perfluorocarbon and tetrafluoroethylene. In addition, modified products, mixtures, or copolymers of these resins may be used. These binders can be used alone or in combination. From the viewpoint of cost and environmental protection, it is preferable that the binder does not contain fluoride.

[0053] The binder resin may be a curable resin that undergoes a curing (crosslinking) reaction after the binder resin is applied to a substrate. The binder resin may be a soluble resin that dissolves in an aqueous or non-aqueous solvent or a dispersion-type resin fine particle. Dispersion-type resin fine particles are resin fine particles that do not dissolve in an aqueous or non-aqueous dispersion medium and exist in the form of fine particles, and the dispersion is generally called an emulsion. These may be used alone or in combination of two or more.

[0054] The particle structure of the dispersion type resin fine particles can be a multi-layer structure, so-called core-shell particles. For example, by localizing a resin obtained by mainly polymerizing a monomer having a functional group in the core or shell, or by providing a difference in Tg or composition between the core and the shell, it is possible to improve the curability, drying property, film-forming property, and mechanical strength of the binder. From the viewpoint of binding property and particle stability, the average particle diameter of the resin fine particles is preferably 10 to 1000 nm, and more preferably 10 to 300 nm. In addition, since the stability of the particles is impaired when a large amount of coarse particles exceeding 1 μm are contained, it is preferable that the amount of coarse particles exceeding 1 μm is at most 5% or less. The average particle diameter can be measured as follows. Depending on the solid content of the resin fine particles, the resin fine particles are diluted 200 to 1000 times with the same dispersion liquid as the dispersion medium. About 5 ml of the diluted dispersion liquid is poured into the cell of a measuring device (Nanotrack manufactured by Nikkiso Co., Ltd.), and the dispersion medium and the refractive index conditions of the resin according to the sample are input, and then the measurement is performed. The particle size can be measured based on the peak of the volume particle size distribution data (histogram) obtained at this time.

[0055] The dispersed resin particles preferably contain crosslinked resin particles. The crosslinked resin particles refer to resin particles having an internal crosslinked structure (three-dimensional crosslinked structure), and it is important that the particles are crosslinked inside. In addition, the crosslinked resin particles contain specific functional groups, which can contribute to adhesion with other electrode constituent materials and substrates. Furthermore, excellent durability can be obtained by adjusting the amount of the crosslinked structure and functional groups.

[0056] The dispersed resin microparticles used are not particularly limited, but examples thereof include (meth)acrylic emulsions, nitrile emulsions, urethane emulsions, diene emulsions (such as SBR (styrene butadiene rubber)), and fluorine-based emulsions (such as PVDF (polyvinylidene fluoride) and PTFE (polytetrafluoroethylene)).

[0057] (solvent) When the nitrogen-doped carbon material and the binder in the conductive composition are mixed uniformly, a solvent may be appropriately used, such as an organic solvent or water. The organic solvent may be an appropriate one depending on the composition of the conductive composition from among alcohols such as methanol, ethanol, propanol, butanol, ethylene glycol methyl ether, diethylene glycol methyl ether, etc., ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc., ethers such as tetrahydrofuran, dioxane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, etc., hydrocarbons such as hexane, heptane, octane, etc., aromatics such as benzene, toluene, xylene, cumene, etc., esters such as ethyl acetate, butyl acetate, etc. Two or more kinds of solvents may be used.

[0058] Furthermore, the conductive composition may contain, as required, conductive materials other than the nitrogen-doped carbon material, thickeners, dispersants, film-forming assistants, antifoaming agents, leveling agents, preservatives, pH adjusters, and the like.

[0059] (Composition ratio of conductive composition) In the conductive composition of the present invention, the ratio of the nitrogen-doped carbon material, the binder, and the solvent is not particularly limited and can be appropriately selected within a wide range. The content of the nitrogen-doped carbon material is preferably 50 to 99.9 mass%, more preferably 70 to 99 mass%, relative to 100 mass% of the total solid content of the conductive composition, in terms of electrical conductivity, adhesion to a substrate, etc. When the content of the nitrogen-doped carbon material is 50 mass% or more, an electronic path in the conductive film is developed, and sufficient electrical conductivity is obtained. The content of the binder is preferably 0.1 to 40% by mass, more preferably 1 to 20% by mass, based on 100% by mass of the total solid content of the conductive composition. When the content of the binder is 0.1% by mass or more, the bonding between the particles in the conductive film and the adhesion between the particles and the substrate are strong, and sufficient coating strength is obtained. When the content of the binder is 40% by mass or less, an electronic path is developed by the nitrogen-doped carbon material and conductive materials other than the nitrogen-doped carbon material in the conductive film, and sufficient conductivity is obtained.

[0060] The appropriate viscosity of the conductive composition depends on the method of coating the composition, but is generally preferably 10 mPa·s or more and 30,000 mPa·s or less.

[0061] <Dispersing machine / mixer> As the apparatus used in obtaining the composition of the present invention, a dispersing machine or a mixer which is usually used for dispersing pigments or the like can be used.

[0062] For example, mixers such as Disper, Homomixer, or Planetary Mixer; homogenizers such as M-Technique's "Clearmix" or PRIMIX's "Filmix"; media-type dispersers such as paint shaker (Red Devil), ball mill, sand mill (Shinmaru Enterprises' "Dynomill", etc.), attritor, pearl mill (Eirich's "DCP Mill", etc.), or Coball mill; media-less dispersers such as wet jet mills (Zenus PY, Sugino Machine's "Starburst", Nanomizer, Nanomizer, etc.), M-Technique's "Clear SS-5", or Nara Machine's "MICROS", or other roll mills, but are not limited thereto. In addition, it is preferable to use a disperser that has been treated to prevent metal from entering the disperser.

[0063] For example, when using a media type disperser, it is preferable to use a method using a disperser whose agitator and vessel are made of ceramic or resin, or a disperser whose metallic agitator and vessel surface are treated with tungsten carbide spraying or resin coating. As the media, it is preferable to use ceramic beads such as glass beads, zirconia beads, or alumina beads. Also, when using a roll mill, it is preferable to use a ceramic roll. Only one type of dispersing device may be used, or multiple types of devices may be used in combination.

[0064] <Conductive film> The conductive film of the present invention is obtained by forming a conductive composition into a film shape, and may be formed, for example, on a sheet-shaped substrate. Alternatively, the conductive composition may be rolled into a sheet shape.

[0065] (Sheet-shaped substrate) The shape of the sheet-like substrate used for forming the conductive film is not particularly limited, but an insulating resin film is preferable, and one suitable for various applications can be appropriately selected.

[0066] For example, the material may be PET (polyethylene terephthalate), PEN (polyethylene naphthalate), polyimide, polyvinyl chloride, polyamide, nylon, OPP (oriented polypropylene), CPP (unoriented polypropylene), etc., but is not particularly limited.

[0067] As for the shape, a flat film is generally used, but substrates with a roughened surface, those treated with a primer, those with holes, and those in a mesh shape can also be used.

[0068] The method for applying the conductive composition onto the sheet-like substrate is not particularly limited, and any known method can be used.

[0069] Specific examples of the coating method include die coating, dip coating, roll coating, doctor coating, knife coating, spray coating, gravure coating, screen printing, and electrostatic painting. Drying methods that can be used include, but are not limited to, standing to dry, blowing dryers, hot air dryers, infrared heaters, and far-infrared heaters.

[0070] After coating, rolling treatment may be performed using a lithographic press or a calendar roll, or heating may be performed to soften the conductive film and make it easier to press. The thickness of the conductive film is generally 0.1 μm or more and 1 mm or less, and preferably 1 μm or more and 200 μm or less. EXAMPLES

[0071] The present invention will be described in more detail below with reference to examples. Note that "parts" refers to parts by mass unless otherwise specified.

[0072] <Nitrogen-doped carbon materials> [Example 1] A mixture was obtained by dry mixing 80 parts of spherical natural graphite (CGB-50, average particle size 50 μm, manufactured by Nippon Graphite Industries Co., Ltd.) as a carbon source and 20 parts of cobalt phthalocyanine (manufactured by Tokyo Chemical Industry Co., Ltd.) as a nitrogen source in a planetary centrifugal mixer. The mixture was filled into an alumina crucible and heat-treated at 1000°C for 1 hour in a nitrogen atmosphere to obtain a nitrogen-doped carbon material (1).

[0073] [Example 2] 80 parts of spherical natural graphite (CGB-50, average particle size 50 μm, manufactured by Nippon Graphite Industries Co., Ltd.) as a carbon source, 20 parts of iron phthalocyanine (manufactured by Sanyo Pigment Co., Ltd.) as a nitrogen source, and 300 parts of ethanol as a solvent were wet mixed in a bead mill and dried in an oven at 70°C under atmospheric conditions to obtain a mixture. The above mixture was filled into an alumina crucible and heat-treated at 1000°C for 1 hour under a nitrogen atmosphere to obtain a nitrogen-doped carbon material (2).

[0074] [Examples 3 to 23, Comparative Examples 1 to 10] Nitrogen-doped carbon materials (3) to (33) were produced using the raw materials and conditions shown in Tables 1 to 4 in the same manner as in Example 1 when the raw materials were dry mixed, and in the same manner as in Example 2 when the raw materials were wet mixed.

[0075] [Table 1] [Table 2] [Table 3] [Table 4]

[0076] The nitrogen-doped carbon materials obtained in the examples and comparative examples were subjected to the following measurements. The results are shown in Tables 5 to 8.

[0077] <Nitrogen content in carbon materials> The carbon and nitrogen element contents in the carbon material were measured using a CHN elemental analyzer (Model 2400, manufactured by PerkinElmer), and the ratio of the nitrogen element content to the carbon element content (N / C) was calculated.

[0078] <Analysis of elements and chemical state on the surface of carbon materials> The ratio of N3 type nitrogen atoms to the total nitrogen amount (surface N 3 ), the ratio of nitrogen to carbon (surface N / C), the amount of surface terminal nitrogen, and the amount of surface metal were evaluated.

[0079] <Basic structure of carbon hexagonal mesh plane> An X-ray diffractometer (Smartlab manufactured by Rigaku Corporation) was used to measure CuKα radiation as an X-ray source, and the half-width of the peak of the (002) plane originating from the graphite skeleton, which appears in the vicinity of 2θ=24.0 to 27.0°, was determined.

[0080] <Specific surface area> Nitrogen adsorption was measured using a gas adsorption measurement device (Microtrack-Bel BELSORP-mini), and the specific surface area was calculated by the BET method.

[0081] The carbon materials obtained in the examples and comparative examples were evaluated as follows. The results are shown in Tables 5 to 8.

[0082] <Powder resistance> The volume resistivity of the carbon material was measured using a powder resistivity measurement system (MCP-PD51 manufactured by Nitto Seiko Analytech Co., Ltd.) The volume resistivity was calculated by adding the carbon material to the measurement cell and then applying a load of 20 kN.

[0083] [Table 5] [Table 6] [Table 7] [Table 8]

[0084] In the examples, the ratio of the nitrogen element content to the carbon element content in the carbon material (N / C) was 0.01 to 20 mol% compared to the comparative examples 1 to 3, 5, and 7 to 10, and the amount of nitrogen doped was appropriate, so that the volume resistivity was improved and the ratio of the volume resistivity of the nitrogen-doped carbon material to the volume resistivity of the raw material was less than 0.9. In addition, in the examples, the ratio of the amount of N3-type nitrogen atoms to the total amount of nitrogen on the carbon material surface (surface N 3 ) is 10 mol % or more, the carrier is efficiently doped, the volume resistivity is improved, and the ratio of the volume resistivity of the nitrogen-doped carbon material to the volume resistivity of the raw material is less than 0.9. Furthermore, compared to Examples 5, 8, 14, and 19, in the other Examples, N / C was 0.1 to 1 mol %, and the carrier density was improved and the crystallinity was high, so that the volume resistivity was further improved. In addition, compared to Example 20, in Example 18, the surface N 3 Since the surface N is 20 mol % or more, the volume resistivity is further improved. 3 Since the content of the CrN alloy was 50 mol % or more, the volume resistivity was further improved. Furthermore, compared to Examples 6, 8, 9, 14, and 21, in the other Examples, the surface N / C was 0.2 to 1.3 mol %, so the surface carrier density was optimal and the volume resistivity was further improved. Furthermore, in comparison with Examples 14 and 17, in Examples 15 and 16, the amount of surface terminal nitrogen was 1 mol % or less, so that inhibition of electrical conductivity was suppressed and the volume resistivity was further improved. Furthermore, compared with Examples 12 and 18 to 23, Examples 1 to 11 and Examples 13 to 17 have a peak half-width and a specific surface area of ​​the (002) plane that are within the preferred ranges, and therefore have a volume resistivity of 2 mΩ cm or less, making them particularly suitable for use as a conductive filler.

[0085] <Conductive composition and conductive film> [Example 24] 12 parts of nitrogen-doped carbon material (1), 3 parts of nitrogen-doped carbon material (23), 5 parts of polyester resin (Vylon 200 manufactured by Toyobo Co., Ltd.) as a binder, and 80 parts of toluene / methyl ethyl ketone / 2-propanol (1 / 1 / 1 (mass ratio)) as a solvent were mixed in a mixer and further dispersed in a sand mill to obtain a conductive composition (1). The obtained conductive composition (1) was applied to a PET film having a thickness of 100 μm as a sheet-like substrate using a doctor blade, and then heated and dried, and the thickness of the conductive film was adjusted to 30 μm to produce a conductive film (1). The volume resistivity of the conductive film (1) was measured by a four-terminal method (JIS-K7194) using a resistivity measuring device (Loresta GP manufactured by Nitto Seiko Analytech Co., Ltd.). The volume resistivity of the conductive film (1) was 2.8 mΩ·cm.

[0086] [Example 25] 18 parts of nitrogen-doped carbon material (4), 50 parts of a carboxymethylcellulose aqueous solution (solid content 2% by mass) as a thickener, and 30 parts of water as a solvent were mixed in a mixer, and further dispersed in a sand mill. Then, 2 parts of an acrylic resin dispersion solution (W-168 manufactured by Toyochem Co., Ltd., solid content 50% by mass) which is a dispersion type resin fine particle was added as a binder and mixed in a mixer to obtain a conductive composition (2). A conductive film (2) was produced in the same manner as in Example 24, except that the conductive composition (2) was used instead of the conductive composition (1). The volume resistivity of the conductive film (2) was 4.1 mΩ·cm.

[0087] [Comparative Example 11] A conductive composition (3) and a conductive film (3) were prepared in the same manner as in Example 24, except that the nitrogen-doped carbon material (21) was used instead of the nitrogen-doped carbon material (1) and the nitrogen-doped carbon material (27) was used instead of the nitrogen-doped carbon material (23). The volume resistivity of the conductive film (3) was 9.4 mΩ cm.

[0088] [Comparative Example 12] A conductive composition (4) and a conductive film (4) were prepared in the same manner as in Example 25, except that spheroidized graphite CGB-50 (manufactured by Nippon Graphite Industries Co., Ltd.) was used instead of the nitrogen-doped carbon material (4). The volume resistivity of the conductive film (4) was 6.4 mΩ cm.

[0089] Compared with Comparative Examples 11 and 12, in Examples 24 and 25, the nitrogen-doped carbon material of the present invention was used, and thus coating films having good volume resistivity were obtained.

Claims

1. A carbon material doped with nitrogen elements to substitute for at least a portion of carbon elements in a carbon skeleton, the ratio of nitrogen elements to carbon elements in the carbon material (N / C) being 0.01 to 20 mol %, and the ratio of N3 type nitrogen atoms to total nitrogen on the surface of the carbon material (surface N 3 % or more of a carbon material (excluding those used for biofuel cell anodes and enzyme cell cathodes).

2. The ratio (mol %) of nitrogen elements to all elements on the carbon material surface measured by X-ray photoelectron spectroscopy (XPS) is defined as N, and the sum (mol %) of the ratio of N1 type nitrogen atoms and the ratio of N2 type nitrogen atoms to all nitrogen on the carbon material surface is defined as (N 1 +N 2 ), then, {N × (N 1 +N 2 2. The carbon material according to claim 1, wherein the proportion of surface terminal nitrogen represented by the formula {(a) / (b)} is 1 mol % or less.

3. 3. The carbon material according to claim 1, wherein the ratio of nitrogen elements to carbon elements on the surface of the carbon material (surface N / C) measured by X-ray photoelectron spectroscopy (XPS) is 0.2 to 1.3 mol %.

4. BET specific surface area with nitrogen as the adsorbed species (BET N2 ) is 0.01 to 100 m 2 The carbon material according to any one of claims 1 to 3, characterized in that:

5. 5. The carbon material according to claim 1, wherein in an X-ray diffraction pattern obtained using CuKα radiation as an X-ray source, the carbon material has a peak at a diffraction angle (2θ) of 24.0 to 27.0°, and the half-value width of the peak is 8° or less.

6. A conductive composition comprising the carbon material according to any one of claims 1 to 5 and a binder.

7. A conductive film obtained by using the conductive composition according to claim 6.

Citation Information

Patent Citations

  • Electroconductive thermoplastic resin composition and production thereof

    JP1991007740A

  • Conductive paste, circuit board using the same, and electronic / electric device

    JP2008293821A

  • Electrode for electric double layer capacitor, method of manufacturing same, and electrode for electric double layer capacitor using same

    JP2010135647A

  • Carbon catalyst and manufacturing method thereof, and catalyst ink and fuel battery arranged by use of carbon catalyst

    JP2014207220A

  • Oxygen gas diffusion electrode and method for manufacturing the same

    JP2014522076A